Occurrence and management of Apple fruit moth in dry temperate zone - Vashisth, Sumit; Sharma, Upinder; Gautam, Nidhish; Verma, Sudhir (Indian Horticulture, 2022)
Apple fruit moth cause damage to apple fruit during early to mid stage of fruit development causing considerable losses in yield. The attack by apple fruit moth larvae at early fruit stage is more serious and they sometimes cause complete crop failure by deforming the fruits, rendering them with no economic value. Insecticides applied to the foliage are usually recommended when apple fruit is in initial development stage.